Dietary patterns and diabetic microvascular complications risk: a Mendelian randomization study of European ancestry - Zhou, Xin; Zheng, Wenbin; Kong, Wen; Zeng, Tianshu (Frontiers in Nutrition, 2024)
Purpose Previous observational studies about the link between dietary factors and diabetic microvascular complications (DMCs) is controversial. Thus, we systemically assessed the potential causal relationship between diet and DMCs risk using Mendelian randomization (MR) methods. Methods We used genome-wide association studies (GWAS) statistics to estimate the causal effects of 17 dietary patterns on three common DMCs in European. Summary statistics on dietary intakes were obtained from the UK biobank, and data on DMCs [diabetic retinopathy (DR), diabetic nephropathy (DN), and diabetic neuropathy (DNP)] were obtained from the FinnGen Consortium. A two-sample MR (TSMR) was conducted to explore the causal relationships of dietary habits with DMCs. In addition, multivariable MR analysis (MVMR) was performed to adjust for traditional risk factors for eating habits, and evaluated the direct or indirect effects of diet on DMCs. Results TSMR analysis revealed that salad/raw vegetable intake (odd ratio [OR]: 2.830; 95% confidence interval [CI]: 1.102 - 7.267; P = 0.0306) and fresh fruit intake (OR: 2.735; 95% CI: 1.622- 4.611; P = 0.0002; false discovery rate [FDR] = 0.0082) increased the risk of DR, whereas cheese intake (OR: 0.742; 95% CI: 0.563 - 0.978; P = 0.0339) and cereal intake (OR: 0.658; 95% CI: 0.444 - 0.976; P = 0.0374) decreased the risk of DR. Salad/raw vegetable (OR: 6.540; 95% CI: 1.061 - 40.300; P = 0.0430) and fresh fruit consumption (OR: 3.573; 95% CI: 1.263- 10.107; P = 0.0164) are risk factors for DN, while cereal consumption (OR: 0.380; 95% CI: 0.174 - 0.833; P= 0.0156) is the opposite. And genetically predicted higher pork intake increased the risk of DNP (OR: 160.971; 95% CI: 8.832–2933.974; P = 0. 0006; FDR = 0.0153). The MVMR analysis revealed that cheese intake may act as an independent protective factor for DR development. Moreover, fresh fruit intake, salad/raw vegetable intake and pork intake may be independent risk factors for DR, DN and DNP, respectively. Other causal associations between dietary habits and DMCs risk may be mediated by intermediate factors. Conclusions This causal relationship study supports that specific dietary interventions may reduce the risk of DMCs.